How Far above the True Anatomic Position can the Acetabular Cup be Placed in Total Hip Arthroplasty?. Issue 2 (March 2013) - Fukui, Kiyokazu; Kaneuji, Ayumi; Sugimori, Tanzo; Ichiseki, Toru; Matsumoto, Tadami
Introduction: There is controversy about which is more suitable for determining correct socket position in patients with severe bone deficiency of the acetabular roof because of developmental dysplasia of the hip (DDH): the anatomic centre of hip rotation or a high centre. Method: We evaluated the relationship, in 200 hips, between the centre of rotation and presence of the Trendelenburg sign to determine the upper limit of cup position from the standpoint of hip-abductor strength. Results: Of the 200 hips, 20 (10%) showed a positive Trendelenburg sign. There were no statistically significant differences between parameters (the centre of rotation, femoral offset, abductor lever arm) regarding the presence of the Trendelenburg sign except for age at surgery. Patients with a positive Trendelenburg sign were significantly older (64.1 ± 9.4 years) than those with a negative Trendelenburg sign (58.8 ± 7.7 years) (P = 0.01). Conclusions: Our findings indicate that a high centre of hip rotation of up to approximately 30 mm from the inter-teardrop line is a feasible option for patients with DDH from the standpoint of hip-abductor strength if stems are used that allow the restoration of femoral offset and the abductor lever arm.